2011
DOI: 10.1021/ja2068017
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Dynamics of Excess Electron Transfer through Consecutive Thymine Sequence in DNA

Abstract: Charge transfer in DNA is an essential process in biological systems because of its close relation to DNA damage and repair. DNA is also an important material used in nanotechnology for wiring and constructing various nanomaterials. Although hole transfer in DNA has been investigated by various researchers and the dynamic properties of this process have been well established, the dynamics of a negative charge, that is, excess electron, in DNA have not been revealed until now. In the present paper, we directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
72
4
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 41 publications
(18 reference statements)
6
72
4
2
Order By: Relevance
“…In all cases, the absorption features due to the charge-separated state are formed within the first 5 ps. Thus, charge-hopping, which is known to occur on a much longer time scale of 10-100 ps (38,39), cannot explain the results. In all mCU a AU (4 − a) oligonucleotides, we observe not only the mC and A bleach but also a very strong bleach of the bridging base U.…”
mentioning
confidence: 81%
“…In all cases, the absorption features due to the charge-separated state are formed within the first 5 ps. Thus, charge-hopping, which is known to occur on a much longer time scale of 10-100 ps (38,39), cannot explain the results. In all mCU a AU (4 − a) oligonucleotides, we observe not only the mC and A bleach but also a very strong bleach of the bridging base U.…”
mentioning
confidence: 81%
“…, [8] faster than that of HT in DNA. In EET, T is known to be a primal excess-electron carrier, whilst it has been suggested that cytosine (C) is not suitable as an excess-electron carrier because of the rapid protonation of CC À .…”
mentioning
confidence: 89%
“…[5][6][7][8][9] Several research groups have revealed that the excess electron can migrate through DNA by a hopping mechanism. [5][6][7][8] However, there remains only limited information on the rate constant for the hopping of excess electrons in DNA. In our previous paper, we showed that the excess electron can migrate through a consecutive sequence of thymine (T) with time constants of the order of 10 10 s…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] In earlier studies it was shown that the replacement of the natural base pairs by non-hydrogen bonding base surrogates with extended aromatic surfaces such as phenanthrene could have beneficial conducting properties and could overcome the physico-chemical limitations of the natural nucleobases. [5] Regarding the reduction of such base surrogates the choice of the electron injector is crucial for the success of the experiments.…”
mentioning
confidence: 99%